Building A Comprehensive Visual Design For Learning Management System, Malaysia Ministry Of Education Lms As A Case Study - Eswati Azni, Jaafar; Mohd Syaheezam , Asyraq Yamin; Mohd , Faizal Amin (2014)
Usability and visual aesthetic elements play very important roles in the evolution of new media design and could be the key factor in determining the success or reliability of a website/portal. The Ministry of Education is no exception benefited the enjoyment of this positive development; it involves teachers, students, and higher administrations. The need to develop a system, which could engage these parties, has been widely initiated. However in the excitement in doing this, one needs to be aware that it has to meet the user's own acceptance. The pillar of this comparative study started with the development of samples on learning management system from Malaysia and international. It has been evaluated under a set of design and usability criteria, and further on, a comparison of findings was done on the major and minor problems. The analysis showed which elements to enhance and could damage perceptions of portal reliability. During the design development process, a new set of design was proposed and tested among local end users by using prototype tools. This study will propose the best approach from design and usability perspective, which enables the systematic development of our education system, and differing from those found in other by adopting our own cultures and mental models. On the limitation aspect, the research will only focus on visual design without looking into the technology behind it, which may affects on its overall performance. The sample of this research was also taken from students aged between 13 to 18 from local secondary school only. Based from the testing, the researcher believed that most Malaysian students are ready for the new approach of Education via information and communications technology (ICT). It is believed that they have been exposed to current technology evolution, and these groups would easily adapt the changes. Implementation of on-line project should be identified from the initial stage, whether it is in the form of application (SAAS) or portal approach because it will drive the whole thing from main strategy or direction and it would eventually be translated into visual design. At the end we would like to have better understanding in creating effective LMS interface and the coherence of design and usability elements applied onto it